(untitled) (Central Asian Journal of Medical Sciences, 2025)
Objective: This study investigates the influence of organisational climate, professional development, and work outcomes on clinical governance in hospitals, with a focus on the Mongolian healthcare system. Clinical governance is a multidimensional framework that seeks to ensure the continuous improvement of healthcare quality by integrating professional standards, accountability mechanisms, and evidence-based management practices. Despite its recognised importance in international contexts, research on clinical governance in Mongolia remains limited, particularly regarding the organisational factors that shape its effectiveness. Methods: To address this gap, structured questionnaires were administered to 605 hospital staff, representing a diverse range of clinical and administrative roles. Data were collected online between August 2022 and February 2023 to ensure broad participation while minimising disruption to hospital operations. The study employed both SmartPLS 3.0 for structural equation modelling and SPSS 24.0 for descriptive and inferential statistical analyses, enabling robust hypothesis testing and triangulation of results. Results: Three hypotheses were tested concerning the relationship between organisational climate, professional development, work outcomes, and clinical governance. The findings revealed that two hypotheses demonstrated statistically significant positive associations, indicating that supportive organisational environments and opportunities for continuous professional growth enhance clinical governance. Conversely, one hypothesis indicated a negative association, suggesting that adverse work-related pressures may undermine governance outcomes. The study makes several contributions to the literature. Conclusion: Theoretically, it expands the understanding of governance by linking institutional climate and individual development to governance performance. Empirically, it provides rare evidence from a specialised hospital context in Mongolia, contributing to comparative knowledge in global health governance. Practically, the findings suggest that hospital leaders and policymakers should prioritise strengthening organisational climate, investing in professional development, and mitigating negative work pressures to enhance governance effectiveness and ultimately improve clinical outcomes.